A Study on Factors Impeding Online Buying of Household Items in Bangalore City - B., Padmanabh; Jeevananda, S.; Jose, K. G. (Indian Journal of Marketing, 2016)
The tremendous growth of the Internet in India has fuelled the growth of e- commerce in the country. The retail business has been affected like all other businesses. This research paper attempted to study the factors responsible for impeding the online buying of household items by customers. The study was limited to Bangalore city only. The study was conducted during June 2013 and December 2014. The data was collected through questionnaires which were distributed among 500 respondents. Among these, 25 questionnaires were partially filled, and were not included as final responses; 280 completely filled questionnaires were utilized for this study. The non online respondents' profile and descriptive statistics were analyzed. Factor analysis was carried out to find the important factors involved in the non online buying decisions of customers. Some recommendations have been made on the strategies which online retailers can adopt to convert non - online buyers to online buyers of household items by addressing some of their concerns.